If you're completing the square the answer is in the image.
expression
x^2 + 5x - 5=ax^2+bx+c
a=1, b=5, c=-5, and you can solve it that way.
Answer: C
Step-by-step explanation:
Simplify the expression to 2^1/4
Now transform the expression using a^m/n = n root a raised to a power of m.
And that's how you get your answer.
Answer: decreases, 2.65 atm
Step-by-step explanation: it’s explained on edg.
Convert the exponential equation to a logarithmic equation using the logarithm base
(
7
)
7
of the right side
(
1
)
1
equals the exponent
(
0
)
0
.
log
7
(
1
)
=
0
Answer:
a repeating term of .3
Step-by-step explanation:
1/3 = 1 divided by 3
1 divided by 3 = .33333333333333333333
that is called a repeating term
= .3